Laboratory Investigations on Perforation of 30PM Steel Plates - Jacek JANISZEWSKI (Wojskowa Akademia Techniczna, 2016)
In this study, high strength steel plates made of 30PM steel were subjected to 7.62 Armour Piercing projectiles at the ordnance velocity. Several experiments differing considerably in conditions of interaction between projectiles and plates were performed. Selected parameters were measured before, during, and after ballistic tests, and both projectile and plate were subjected to detailed examination. It is foreseen to use the obtained results in two ways. Protection performance of steel plates will be determined and experimental data will be used as a reference for analyzing various models and numerical techniques, accessible in commercially available hydrocodes. The authors present the methodology, the experimental set-up configuration, and the results of laboratory experiments.
Keywords: Balistyka końcowa